On the Track of Road Evolution. (June 2014) - Mouratidis, Anastasios; Kehagia, Fotini
Man's tendency to move began millennia ago, satisfying a basic need for food, shelter, clothing or social interaction. The uncertain path of road construction through the centuries is set forth by the primitive and everlasting need for mobility, trade and communication. In the era of engineering, and mostly technological boost, highways of the fourth generation ensure safe, fast and easy driving. It is difficult to discern deficiencies or drawbacks in the layout of a motorway of the fourth generation. However, weak points still exist. Vehicles moving on motorways consume energy and produce negative impact to the environment either by emissions or by noise. Despite the performance of the motorway, passengers still get trapped on routes by adverse climatic conditions and, even more, by pile-up accidents. The overall challenge for the fifth generation is to provide convincing ideas to handle effectively all these issues. In this article, the history of road from earliest times to the present, from the first to the fifth generation, is presented. The different factors that have influenced the design, development, construction and operation are examined. Moreover, new challenges to be faced and addressed by the roads of fifth generation are presented.